DEVELOPMENT OF INTEGRATION FRAMEWORK OF FORMAL, INFORMAL AND SEMI FORMAL SECTORS IN MUNICIPAL SOLID WASTE MANAGEMENT SYSTEM (CASE STUDY : SOLID WASTE MANAGEMENT SYSTEM IN YOGYAKARTA CITY, SLEMAN AND BANTUL REGENCY) - Purnama Putra, Hijrah
The growth of a city is always followed by a burden that must be accepted by the city, e.g. the total solid waste of urban community. There are two sectors works in the solid waste management system, i.e. (1) the formal sector managed by the government, starting from the activities of storage, collection, transportation, processing to final disposal; and (2) The informal sector carried out by scavengers, collectors, intermediates, dealers, brokers, and others that have a role in solid waste recovery, but is not a considered in the design of municipal solid waste management systems. Currently, in Indonesia, developing another sector, in this study referred to as the semi-formal sector, namely the Solid Waste Bank and TPS 3R. This sector continues to grow but has not been equipped with comprehensive studies to evaluate its performance. This study aims to identify and evaluate the performance of the three sectors as well as the factors that affect their performance, and develop ideas of integration framework of the three sectors in the solid waste management system.